Application of creatinine- and/or cystatin C-based glomerular filtration rate estimation equations in elderly Chinese - Ye, Xiaoshuang (Dove Medical Press, 2014)
BACKGROUND: No conventional creatinine- or cystatin C-based glomerular filtration rate (GFR) estimation equation performed consistently outstandingly in elderly Chinese in our previous studies. This research aimed to further evaluate the performance of some recently proposed estimation equations based on creatinine and cystatin C, alone or combined, in this specific population. MATERIALS AND METHODS: The equations were validated in a population totaling 419 participants (median age 68 [range 60–94] years). The estimated GFR (eGFR) calculated separately by ten equations was compared with the reference GFR (rGFR) measured by the (99m)Tc-DTPA renal dynamic imaging method. RESULTS: Median serum creatinine, cystatin C, and rGFR levels were 0.93 mg/L, 1.13 mg/L, and 74.20 mL/min/1.73 m(2), respectively. The Chinese population-developed creatinine- and cystatin C-based (Cscr-cys) equation yielded the least median absolute difference (8.81 vs range 9.53–16.32, P<0.05, vs the Chronic Kidney Disease Epidemiology Collaboration serum creatinine equation), the highest proportion of eGFR within 15% and 30% of rGFR (P(15) and P(30), 55.13 and 85.44, P<0.05 and P<0.01, vs the Chronic Kidney Disease Epidemiology Collaboration serum creatinine equation), and the lowest root mean square error (14.87 vs range 15.30–22.45) in the whole cohort. A substantial agreement of diagnostic consistency between eGFR and rGFR (with a kappa 0.61–0.80) was also observed with the Cscr-cys equation. Moreover, measures of performance in the Cscr-cys equation were consistent across normal to mildly injured GFR strata and individuals aged ≤80 years. Among all the Cscr-cys equations, the elderly Chinese-developed creatinine-based (CEscr) equation performed best in this specific population. Nevertheless, none of the equations achieved ideal manifestation in the moderately to severely GFR-injured group or in individuals aged ≥80 years. CONCLUSION: The Cscr-cys equation appeared to be optimal in elderly Chinese among the investigated equations. If cystatin C is not available, the CEscr equation is an acceptable alternative. A multicenter study with abundant subjects to develop an apposite formula for elderly Chinese is assumed to be essential.